2006
DOI: 10.1086/505431
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment for Malaria Control Administered at the Time of Routine Vaccinations in Mozambican Infants: A Randomized, Placebo‐Controlled Trial

Abstract: IPTi with SP has been shown to moderately reduce the incidence of clinical malaria in Mozambican infants without evidence of rebound after stopping the intervention or of interactions with EPI vaccines. Its recommendation as a malaria control strategy in Mozambique needs to be balanced against the scarcity of affordable control tools and the burden of malaria in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 17 publications
5
114
0
Order By: Relevance
“…Firstly, recent data on the in vivo efficacy of SP in children in this area have shown a therapeutic efficacy rate of 83%, with a parasitological sensitivity of 78.6% at day 14 [28]. Secondly, SP was highly efficacious for malaria prevention in the study women and in a concurrent study of IPT in infants in the same area, where the efficacy of SP for malaria prevention varied between 60 and 90% in the month after SP administration [29].…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, recent data on the in vivo efficacy of SP in children in this area have shown a therapeutic efficacy rate of 83%, with a parasitological sensitivity of 78.6% at day 14 [28]. Secondly, SP was highly efficacious for malaria prevention in the study women and in a concurrent study of IPT in infants in the same area, where the efficacy of SP for malaria prevention varied between 60 and 90% in the month after SP administration [29].…”
Section: Discussionmentioning
confidence: 90%
“…The resulting "IPTi Consortium" ( www.ipti-malaria.org ), has supported efficacy trials of IPTi in five countries, and together with other groups has generated information on safety, efficacy, potential interactions with the Expanded Program on Immunization (EPI) vaccines, resistance, acceptability, immunology, cost, and cost-effectiveness. [7][8][9][10][11][12][13][14][15][16] A recent independent review of IPTi concluded that "the evidence makes IPTi with sulphadoxine-pyrimethamine a promising public health strategy." 17 Efficacy is defined as the impact achieved by interventions when given in research settings.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent preventive treatment for malaria in infants (IPTi) is a promising new intervention consisting of the administration of a treatment dose of sulfadoxine/pyrimethamine (SP) at the time of routine vaccinations in the first year of life. 3 A pooled analysis 4 of six randomised controlled trials (RCT) of IPTi using SP (IPTi-SP) [5][6][7][8][9][10] suggested that the intervention can reduce the incidence of clinical malaria in the first year of life by 30%. If such an effect can be achieved by delivering an available and affordable antimalarial treatment at the time of routine contacts with the health system, IPTi-SP may become a useful component of antimalarial strategies in some settings.…”
Section: Introductionmentioning
confidence: 99%